Quali etruschi maestri di scrittura? (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2012)
The contributions of this section of the book (M.C. Biella, M. Cantù e A. Gobbi) present study cases  focused on the relation of the inscription to the object, of the inscribed object to its context and on the final visual impact as a whole, in Central Italy during the Orientalising period. Taking into account the results of the three contributors, this contribution aims to study the social aspects of the epigraphic documentation other than the Etruscan. The starting point is the inscribed object studied as a three-dimensional image circulating in a social network. Such an image is created by a multifaceted range of choices concerning: objects, letter forms and alphabetiform signs.As a consequence the inscribed objects could be considered for its considerable role as social indicators in the complex phenomena of building identities in contexts of cultural contact.